Humic Substances in Combination With Plant Growth-Promoting Bacteria as an Alternative for Sustainable Agriculture - da Silva, Maura Santos Reis de Andrade; dos Santos, Bianca de Melo Silveira; da Silva, Camilla Santos Reis de Andrade; da Silva, Carolina Santos Reis de Andrade; Antunes, Luiz Fernando de Sousa; dos Santos, Roberta Mendes; Santos, Carlos Henrique Barbosa; Rigobelo, Everlon Cid (Frontiers in Microbiology, 2021)
Plant growth-promoting bacteria (PGPB) and humic substances (HS) are promising options for reducing the use for pesticides and mineral fertilizers. Although many studies have shown the effects of PGPB and HS separately, little information is available on plant responses to the combined application of these biostimulants despite the great potential for the simultaneous action of these biological inputs. Thus, the objective of this review is to present an overview of scientific studies that addressed the application of PGPB and HS to different crops. First, we discuss the effect of these biostimulants on biological nitrogen fixation (BFN), the various effects of the inoculation of beneficial bacteria combined with the application of HS on promoting the growth of non-leguminous plants and how this combination can increase bacterial colonization of plant hosts. We also address the effect of PGPB and HS on plant responses to abiotic stresses, in addition to discussing the role of HS in protecting plants against pathogens. There is a lack of studies that address the role of PGPB + HS in biocontrol. Understanding the factors involved in the promotion of plant growth through the application of PGPB and HS can assist in the development of efficient biostimulants for agricultural management. This approach has the potential to accelerate the transition from conventional cultivation to sustainable agrosystems.